Laudato si' na presečišču vere, znanosti in etike - naravovarstveno ozadje in izzivi papeževe okrožnice - Dobravec, Jurij (Varstvo narave, 2016)
In 2015, Pope Francis published an important document for nature conservation, the Laudato Si% % On Care For Our Common Home encyclical. The article initially provides a concise presentation of individual emphases and continues with the historic and natural science background of the origin of the text, which allows us to discern that the current leader of the Catholic Church has joined natural science knowledge on nature and the environment, the ethical principles of philosophers and the teachings of his predecessors and contemporaries into an official position. The second part aims at connecting content that is derived from the new teachings of the church and that is close to the subject of modern nature conservation, especially the importance of dialogue, endeavours for common values and man%s inner attitude towards nature. The third part uncovers the parallels between the fully biological cyclical processes in nature and the Pope%s concrete proposals for realising ecological conversion. The final part showcases the exceptional importance of the biological sciences for the realisation of the Pope%s idea of integral ecology.
Keywords: Catholic Church; environmental ethic; environmental protection; etika narave; Katoliška cerkev; Laudato si'; nature conservation; papež Frančišek; Pope Francis; the Catholic Church; varstvo narave